2023
DOI: 10.1186/s12957-023-02915-z
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant PD-1 blockade combined with chemotherapy is not superior to neoadjuvant chemotherapy alone in resectable locally advanced esophageal carcinoma

Abstract: Background Neoadjuvant chemotherapy (nCT) or neoadjuvant chemoradiotherapy followed by surgery has been recommended as standard treatment in patients with locally advanced esophageal cancer (LAEC). But the risk of tumor recurrence still remained, and many patients refused or abandoned radiotherapy because of the intolerable adverse effects in China. Neoadjuvant immunochemotherapy (nICT) followed by surgery has become an emerging treatment in patients with esophageal cancer. There was still no c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…However, the potential long-term prognostic benefits of these pathological response improvements remain unclear. Cheng D et al 28 reported that nICT did not significantly improve DFS in ESCC compared to nCT alone ( P =0.98). However, the median follow-up time in this study was only 22 months.…”
Section: Discussionmentioning
confidence: 98%
“…However, the potential long-term prognostic benefits of these pathological response improvements remain unclear. Cheng D et al 28 reported that nICT did not significantly improve DFS in ESCC compared to nCT alone ( P =0.98). However, the median follow-up time in this study was only 22 months.…”
Section: Discussionmentioning
confidence: 98%